Total Ear Reconstruction Using Porous Polyethylene - Ali, Kausar; Trost, Jeffrey G.; Truong, Tuan A.; Harshbarger, Raymond J., III (Seminars in Plastic Surgery, 2017)
Total ear reconstruction has been approached by several techniques involving autologous graft, prosthetic implant, and alloplastic implant options. Recent studies have shown the superiority of porous polyethylene (Medpor, Porex Surgical) reconstruction over autologous reconstruction based on improved aesthetic results, earlier age of intervention, shorter surgery times, fewer number of required procedures, and a simpler postoperative recovery process. A durable and permanent option for total ear reconstruction, like Medpor, can help alleviate the cosmetic concerns that patients with auricular deformities may be burdened with on a daily basis. In this article, the authors discuss the advantages of Medpor-based ear reconstruction and discuss recent advances in the surgical techniques involved, such as harvesting a temporoparietal fascia flap and full-thickness skin graft to adequately cover the Medpor framework and decrease extrusion rates.
Keywords: ear reconstruction; microtia; polyethylene; Medpor; temporoparietal fascia flap